Comparison of the Effectiveness of 2% Acetic Acid and Mineral Oil on Serum Prop Children of Aisyiyah Orphanage Medan in Vitro - Kasibu, Raja Sun Daffa; Nasution, Muhammad Edy Syahputra (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Serum prop is an accumulation of a substance secreted by the sebaceous glands and seruminous composed also with corneal desquammation from the stratum corneum in the ear canal which can cause symptoms or interfere with the assessment of the ear canal, tympanic membrane, and audiovestibular system. Corrosive acetic acid can destroy serum prop as well as mineral oil as a lubricant that can make cerumen come out of the ear canal. This study aims to analyze the comparison of the effectiveness of 2% acetic acid and mineral oil on serum prop children of the Putri Aisyiyah Orphanage Medan in vitro at 5, 10, 15, and 30 minutes. This study is an in vitro experimental with a quasy experimental type using a simple random sampling technique involving 25 serum prop samples, each sample will be tested with 2% acetic acid and mineral oil with a UV-Vis spectrophotometer. The data collected were analyzed using the ANOVA repeated measures parametric test and the non-parametric Kruskal wallis test. The intervention of 2% acetic acid and mineral oil on in vitro cerumen was most significant at 30 minutes, In comparison the effectiveness of 2% acetic acid was obtained higher results than mineral oil against in vitro cerumen which was known from the mean difference in each test solution. 2% acetic acid has a higher effectiveness against in vitro serum intervention compared to mineral oil.